2003
DOI: 10.1021/jm021118o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 14-Alkoxymorphinans. 18. N-Substituted 14-Phenylpropyloxymorphinan-6-ones with Unanticipated Agonist Properties:  Extending the Scope of Common Structure−Activity Relationships

Abstract: The synthesis, biological, and pharmacological evaluations of 14beta-O-phenylpropyl-substituted morphinan-6-ones are described. The most striking finding of this study was that all of the compounds from the novel series of differently N-substituted 14beta-O-phenylpropylmorphinans acted as powerful opioid agonists. Even with N-substituents such as cyclopropylmethyl and allyl, which are usually associated with distinct antagonist properties, only agonists were obtained. Compared to morphine, the N-cyclopropylmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
65
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 25 publications
9
65
1
Order By: Relevance
“…Recently, we have reported that the introduction of a 14-phenylpropoxy group gives rise to extremely potent analgesics in morphinan-6-ones having a methyl, cyclopropylmethyl, or allyl group at the morphinan nitrogen. 10,16 Thus, it became apparent that 14-arylalkoxy substitution increases analgesic potency compared to 14-alkoxymorphinans such as 14-O-methyloxymorphone (1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported that the introduction of a 14-phenylpropoxy group gives rise to extremely potent analgesics in morphinan-6-ones having a methyl, cyclopropylmethyl, or allyl group at the morphinan nitrogen. 10,16 Thus, it became apparent that 14-arylalkoxy substitution increases analgesic potency compared to 14-alkoxymorphinans such as 14-O-methyloxymorphone (1).…”
Section: Resultsmentioning
confidence: 99%
“…(19) Similar results were provided on differently N -substituted 14-phenylpropoxymorphinan-6-ones (e.g., N -allyl and N -cyclopropylmethyl substituted morphinans 5 and 6 ). (20) It was established that the presence of a 14-phenylpropoxy group increases both the agonist potency and the affinity for all three opioid receptor types while concurrently diminishing the selectivity for any of the receptors. The two classical opioid antagonists naloxone ( 7 ) and naltrexone ( 8 ) were converted into highly active analgesic agents by introducing a phenylpropoxy group in position 14 (compounds 5 and 6 , respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The two classical opioid antagonists naloxone ( 7 ) and naltrexone ( 8 ) were converted into highly active analgesic agents by introducing a phenylpropoxy group in position 14 (compounds 5 and 6 , respectively). (20) Moreover, derivatives of the selective μ opioid receptor antagonist cyprodime having a phenylpropoxy group at C-14 have also acted as potent antinociceptives in different pain models in mice after subcutaneous (sc) administration. (21) Thus, the presence of this substituent directs to a profound alteration in the pharmacological profile of morphinan-6-ones.…”
Section: Introductionmentioning
confidence: 99%
“…Similar discrepant results have also been observed by other research groups. 50 We also noticed that the introduction of a substitution at the 14-position of morphinan skeleton could be crucial in altering the pharmacological profile 51 while the orientation (in the manner of rotation freedom) of such substitution at this position may lead to high potency MOR agonism activity during the development of some pseudo-irreversible opioid receptor antagonists. 52-54 In combination of our observation, a more vivid picture of 14-substitution impact on the pharmacology of morphinan skeleton derivatives is now available.…”
Section: Resultsmentioning
confidence: 99%